Hidden in plain sight: Sam Goudie and the Ontario Mennonite Brethren in Christ - Fuller, James Clare (McMaster Divinity College general series, 2024)
The Evangelical Missionary Church in Ontario was born out of the Canadian Mennonite church modified by Wesleyan holiness revivalism in the nineteenth century. Sam Goudie (1866-1951), from a Scottish and Swiss-German Mennonite family in Waterloo County, led the Ontario Conference of the Mennonite Brethren in Christ Church through the period of the formation of the Pentecostal movement, establishment of a western Canadian conference, and the First World War. With Goudie's support, the rural denomination attempted to evangelize small-town Ontario through teams of women preachers with some success until the Depression. Goudie also led in the formation of the denominational mission, beginning in Nigeria, adding missions in India and the Middle East during his presidency. He also chaired the Executive Committee of the binational MBiC church for over thirty years. This book clarifies the relation of the MBiC to the parent Mennonite Church and corrects some of the prevailing stories of early Pentecostalism in Canada. It explores differences between collectivist denominational life in the denomination's first generations shared with other rural holiness Canadian churches and the congregationalist culture of twenty-first-century evangelical Canadian Christianity